Problems of Teaching Drawing at School - Qosimova Nilufar Muratjon qizi; Sharabayev Ulug'bek Muhammedovich (Research Parks Publishers, 2022)
This article deals with the problems of teaching drawing in school, which focuses on the important tasks of general secondary school in developing independent and creative thinking, the ability to work independently, which are important qualities of students.